Chronic Cannabigerol as an Effective Therapeutic for Cisplatin-Induced Neuropathic Pain - Rahul Nachnani; Diana E. Sepulveda; Jennifer L. Booth; Shouhao Zhou; Nicholas M. Graziane; Wesley M. Raup-Konsavage; Kent E. Vrana (MDPI AG, 2023)
Cannabigerol (CBG), derived from the cannabis plant, acts as an acute analgesic in a model of cisplatin-induced peripheral neuropathy (CIPN) in mice. There are no curative, long-lasting treatments for CIPN available to humans. We investigated the ability of chronic CBG to alleviate mechanical hypersensitivity due to CIPN in mice by measuring responses to 7 and 14 days of daily CBG. We found that CBG treatment (i.p.) for 7 and 14 consecutive days significantly reduced mechanical hypersensitivity in male and female mice with CIPN and reduced pain sensitivity up to 60-70% of baseline levels (p < 0.001 for all), 24 h after the last injection. Additionally, we found that daily treatment with CBG did not evoke tolerance and did not incur significant weight change or adverse events. The efficacy of CBG was independent of the estrous cycle phase. Therefore, chronic CBG administration can provide at least 24 h of antinociceptive effect in mice. These findings support the study of CBG as a long-lasting neuropathic pain therapy, which acts without tolerance in both males and females.